Loss of Brca1 Induces Senescence of Murine Ovarian Fibroblasts and May Contribute to Fibroblast-Mediated Ovarian Aging - Vaishnav, Het (Université d'Ottawa / University of Ottawa, 2023)
Ovarian cancer, primarily diagnosed at advanced stages of the disease, is the most lethal of all gynaecological malignancies, with a 5-year survival of only 45%. Increasing age and number of ovulations are the primary non-hereditary risk factors, with the median age of onset being 63 years. Considering that risk peaks upon onset of menopause and that 50% of all cases of ovarian cancer have non-ovarian origins, it is believed that the physiological aging of the ovary renders it an appealing pre-metastatic niche. Mutations in the tumor suppressor genes BRCA1 and BRCA2 are the primary hereditary risk factors, accounting for 20-25% of all cases. We have preliminary data showing that BRCA1 mutation carriers tend to develop ovarian fibrosis, a phenomenon that naturally accompanies ovarian aging, at premenopausal ages, whereas age-associated fibrosis becomes evident after menopause in non-carriers. Consistently, BRCA1/2 mutation carriers are at elevated risk for premature cessation of ovarian function. With the median age of cancer onset decreasing from 63 to 50 years of age in BRCA1 mutation carriers, these data collectively suggest accelerated ovarian aging in these women and highlights an association between ovarian aging and increased risk for cancer. As such, we hypothesized that loss of Brca1 in murine ovarian fibroblasts (MOFs) may accelerate the onset of ovarian fibrosis through fibroblast hyperactivation, contributing to ovarian aging. Using primary MOFs isolated from Brca1 LoxP/LoxP mice and adenoviral cre mediated recombination, we generated Brca1 deficient MOFs. RNA sequencing was used to characterize the transcriptomic changes associated with the loss of Brca1. Our findings suggest that Brca1 deficiency in MOFs induces cellular senescence and enhances their myofibroblastic function, likely yielding increased stiffness of the ovarian extracellular matrix due to the dysregulated synthesis and degradation of its constitutive components, contributing to accelerated ovarian aging.
Keywords: Ovarian cancer; Mutation carriers